(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The paper analyzes the long-term and short-term strategic and program documents of the Central Asian countries on water policy. The key national strategies and programs of Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan and Turkmenistan, determining the tasks of these countries in water policy are identified and studied. The President’s Address’ to the people and the parliament are analyzed. Official statements of the heads of states allow to define a vision of further sharing of transboundary water resources in the region. The key points of policy documents on interregional cooperation in the field of distribution of transboundary water resources are considered. A comparative analysis is carried out the points relating to the development of international cooperation for the protection and efficient use of the transboundary rivers. The positions of countries on the further use of the transboundary rivers based on the long-term and short-term tasks of the state of development are revealed. The article contains the conclusions on the main trends in the development of transboundary water cooperation in Central Asia. Key words: transboundary water resources, strategic documents of the Central Asian countries, water policy.